Effect of formative feedback on human anatomy learning: a mixed-methods study on student perceptions and academic performance - Arroyo, Noelia; Quizás, Constanza; Rubilar-Cuevas, Jorge; Salinas, Paulo (Frontiers in Education, 2025)
BackgroundFormative feedback (FF) is a key pedagogical tool in anatomy education, aiming to enhance learning by fostering self-regulation, motivation, and conceptual understanding. However, its effectiveness in improving academic performance remains inconclusive.ObjectiveThis study investigates the impact of FF on student perceptions and academic performance in an undergraduate anatomy course using a mixed-methods approach.MethodsA convergent parallel design was employed, integrating qualitative and quantitative analyses. Qualitative data from open-ended questionnaires and focus groups were analyzed through thematic coding using ATLAS.ti, resulting in 140 initial codes, later refined into 34 key themes. A coding network was constructed to map students' perceptions. Quantitative analysis compared students' pre- and post-feedback academic performance using paired Student's t-tests in GraphPad Prism 9.0.ResultsQualitative findings indicate that students perceive FF as beneficial for reinforcing anatomical concepts, improving study techniques, and fostering self-regulated learning. However, concerns about superficiality, lack of specificity, and cognitive overload were frequently mentioned. Quantitative analysis revealed no significant differences in grades before and after FF implementation, suggesting that while FF is valued by students, it does not necessarily translate into measurable academic gains in the short term.ConclusionFF positively impacts student engagement, motivation, and learning strategies, yet its academic benefits may depend on feedback structure, specificity, and integration into assessment frameworks. Enhancing dialogic and visually supported feedback mechanisms may optimize FF's effectiveness in anatomy education.